Mapping in the Oiapoque Indigenous Territories - Rosélis Remor de Souza Mazurek (Revue d'ethnoécologie)
Participatory mapping for land use planning in the Indigenous Territories (Terras Indígenas) of Oiapoque, in northeastern Amazonia has been carried out by governmental and non-governmental organizations in partnership with indigenous institutions. The first mapping exercise was carried out through regional workshops with a selected group of indigenous (Indigenous Environmental Agents) using a georeferenced Landsat satellite image and drawing physical and cultural aspects of the territory over the images on paper. In this study, we document an alternative approach started at the village level, included more time consulting with diverse members from the community and collective field visits to sites within the indigenous land. This experience was carried out in ten villages in the Uaçá, Juminã, and Galibi Indigenous Territories (Amapá, Brazil) from October 2013 to August 2014. Results showed detailed classification of the landscape into 13 different local categories of land use and management. The collective mapping process allowed people to reflect and analyze together their current land use and existing management practices. Fields visits were an important aspect of the methodology as for promoting intergenerational exchange of traditional knowledge. The comparison of the two mapping exercises suggests that focus on particular segments of society might achieve limited success if not associated with other strategies to strengthen their interaction with the villages in the long term. Finally, the study questions current practices: what remains of mapping exercises in the community? Do they lead to a better political organization and/or environmental consciousness? Mapping for Territorial Management as conducted here seems to offer the additional and important opportunity to retrieve, remember, discuss and register the history of the community.